Educational Program on the Introduction and Use of a Microbiology Kit for Students at State Vocational High School 6, Ambon City - Brian Saputra Manurung; Windy Natalia Nusaly; Synodalia Ch Wattimena; Jecklyn Shindy Temartenan (Talenta Publisher Universitas Sumatera Utara, 2026)
Microbiology is a field of science that studies microorganisms. Microorganisms in nature play many roles in life, both beneficial and harmful. A comprehensive understanding of the basic concepts of microbiology is essential for academics, practitioners, clinicians, and the general public, including students. This educational activity aims to provide students at State Vocational High School 6 in Ambon City with an understanding of microbiological concepts, both theoretical and practical. Limited laboratory facilities and practical equipment often pose a challenge for schools, especially vocational high schools. An understanding of microbiological concepts, both in theory and practice, is expected to equip students to apply their knowledge of microorganisms and improve their skills in conducting simple observations or identifying microbes using a microbiology kit. The method used in implementing the Community Service Program (CSP) at State Vocational High School 6, Ambon City, involved outreach activities packaged as hands-on educational sessions on the Introduction to Microbiology Kits. This community service program yielded theoretical understanding and practical skills in performing microbiological work among students, as evidenced by evaluation responses after following and conducting the microbiological work program. This educational activity supports the government and Universitas Pattimura through the involvement and role of lecturers and students in the community, as well as enhances the application of scientific knowledge and skills in microbiological work to meet the needs and challenges of producing competent, reliable, and integrity-driven human resources to further support the development of Maluku.